2001
DOI: 10.1007/s004170000250
|View full text |Cite
|
Sign up to set email alerts
|

Role of inhibitors of isoprenylation in proliferation, phenotype and apoptosis of human retinal pigment epithelium

Abstract: We identified various effects of lovastatin on human RPE cultures: inhibition of cell proliferation, modifications of the phenotype and induction of apoptosis. Interestingly, the addition of different inhibitors of protein isoprenylation only affected the proliferation of the cells. There was no evidence that isoprenylated proteins inhibition is related to lovastatin-induced RPE apoptosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
1

Year Published

2002
2002
2011
2011

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 40 publications
(46 reference statements)
0
4
1
Order By: Relevance
“…Thrombin has been shown to activate the classic Ras-dependent MAPK pathway in human [16] and canine [20] tracheal smooth muscle cells. Our results, however, showed that thrombin-induced ERK phosphorylation in RPE cells bypasses Ras, since it was not prevented by the Ras farnesylation inhibitor manumycine, which has been shown to suppress the membrane anchoring of Ras [59] and Ras activation by serum in RPE cells [60].…”
Section: Discussioncontrasting
confidence: 58%
“…Thrombin has been shown to activate the classic Ras-dependent MAPK pathway in human [16] and canine [20] tracheal smooth muscle cells. Our results, however, showed that thrombin-induced ERK phosphorylation in RPE cells bypasses Ras, since it was not prevented by the Ras farnesylation inhibitor manumycine, which has been shown to suppress the membrane anchoring of Ras [59] and Ras activation by serum in RPE cells [60].…”
Section: Discussioncontrasting
confidence: 58%
“…Given the pervasive role of isoprenoids in metabolism, it is not surprising that imbalances in isoprenoid synthesis and utilization can lead to cellular dysfunction and disease. Controlling flux through these pathways is used to prevent and cure human disease; statins, which decrease cellular levels of mevalonate by inhibiting HMG-CoA reductase , , are used widely to control cholesterol levels in humans and may prove useful in the treatment of other diseases .…”
mentioning
confidence: 99%
“…36 Statins affect RPE cell survival and morphology in vitro. 37 The challenge for future laboratory research will be to determine which processes are modulated by statins in vivo and therefore are primarily responsible for the apparent beneficial effects observed in the present study.…”
Section: Discussionmentioning
confidence: 96%